ACTR-64. PHASE 2 STUDY TO EVALUATE THE SAFETY, PHARMACOKINETICS AND CLINICAL ACTIVITY OF PI3K/mTOR INHIBITOR GDC-0084 IN GBM PATIENTS WITH UNMETHYLATED O6-METHYLGUANINE-METHYLTRANSFERASE (MGMT) PROMOTER STATUS. (11th November 2019) - Wen, Patrick; DeGroot, John; Battiste, James; Goldlust, Samuel; Garner, James; Simpson, Jeremy; Kijlstra, Jelle; Olivero, Alan; Cloughesy, Timothy
Abstract: BACKGROUND: GDC-0084 is a potent, oral, selective small molecule inhibitor of class I phosphoinositide 3-kinase and mammalian target of rapamycin (PI3K/mTOR). GDC-0084 crosses the blood-brain barrier and achieves a brain / plasma ratio of approximately 1.0. GDC-0084 was given as once daily dosing in a phase 1 study (Wen et al, J Clin Oncol 34, 2016(15) suppl.2012) in 47 patients with recurrent high-grade gliomas. The adverse events were generally consistent with the established PI3K/mTOR inhibitor class-effects. The MTD identified was 45mg once daily. METHODS: The current study is conducted in the newly diagnosed GBM patient with unmethylated MGMT promotor status upon completion of standard adjuvant XRT/TMZ. It has a 2-part design: an open-label, dose-escalation phase to assess the safety, tolerability, MTD (Part 1, followed by an expansion cohort (Part 2) commencing once MTD is established. Dose-escalation started at 60mg, and progressed in 15mg increments, per standard 3 + 3 rules. Part 2 recruits 20 patients, who are randomized to take GDC-0084 at the identified MTD, in fed and fasted states. RESULTS: Part 1 of the study is complete. There were no DLTs among 3 pts treated at the 60mg. Among 6 pts treated at 75mg, DLTs were identified as hyperglycaemia (symptomatic) and oral mucositis. Adverse effects seen were generally modest, manageable and consistent with the PI3K-class. PK parameters are in line with phase 1 data. Part 2 recruitment is ongoing. CONCLUSION: GDC-0084 displays a safety profile consistent with previous data in recurrent high-grade glioma but appears better tolerated in the newly diagnosed GBM setting. An MTD of 60mg is identified.